DAMPAK MEDIA SOSIAL PADA KINERJA UMKM DI KOTA BANDAR LAMPUNG - Arinda, Anggun Yustia (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2021)
The use of information technology developments is widely used to develop businesses, both from companies and from individuals. The rapid development of digital technology over the last few years has had a major impact on various existing economic actors, including MSME players, to survive and continue to compete. This study examines the impact of social media on the performance of MSMEs in the city of Bandar Lampung. This study uses primary data with a direct survey method involving 100 MSME business actors with various industries in the city of Bandar Lampung. Based on quantitative descriptive analysis and qualitative descriptive analysis, this research finds empirical evidence that social media has a positive effect on sales performance, marketing performance, and interactivity. However, it still has no effect on increasing the number of employees.